USTHURAT MAN'I Al-ZAWAJ BAYNA ANSABI JUMINU WA KURUMAN (BI AN-NADZARIYAT AL-BUNYAWIAT LI CLAUDE LÃ‰VI-STRAUSS WA HADITH AN-NABI) - Muassomah, Muassomah; Yurisa, Penny Respaty (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
In an age of industrial and technological advancements, there are still people who believe in the myth of the prohibition of marriage between the Gomino and Cruman lineages. This myth originated from the battle between troops led by Sindo Joyo and soldiers led by Kidang Palih. Kidang Palih was killed by Sindo Joyo in that battle. Then this myth emerged. This study was analyzed with the structural theory of Claude Levi-Strauss, who examined myths. In this study, researchers also found views from the hadith of the Prophet because in the hadith talking about the prohibition of marriage. According to the research results, the reason for the marriage ban was that the Sindo Joyo and Kidang Palih troops fought until Kidang Palih was killed by Sindo Joyo. Kidang Palih's wife was also killed, he dressed as a man and fought with Sindo Joyo. Claude LÃ©vi-Strauss structurally divides this myth into 8 episodes. There are 5 characters in this myth. Meanwhile, according to the Hadith considered explaining that there is no hadith that prohibits marriage according to lineage. But offspring are taken into consideration when choosing a husband or wife.